398 Impact of a laparoscopic triage program for advanced ovarian cancer on surgical outcomes, disease-free survival, and overall survival. (13th November 2020) - Mulder, I; Fleming, N; Sun, C; Fellman, B; Ulin, L; Ozer, M; Coleman, R; Ramirez, P; Rangel, K; Soliman, P; Nick, A; Lu, K; et al.
Abstract : Introduction: This study evaluates whether implementing a laparoscopic triage algorithm (LSC) to grade initial disease burden impacts surgical outcomes, disease-free survival (DFS), and overall survival (OS) in advanced ovarian cancer (OC). Methods: In 2013, LSC was implemented for advanced high-grade serous OC. LSC scores volume and distribution of intra-abdominal disease in order to disposition patients to either primary cytoreductive surgery (PDS) or neoadjuvant chemotherapy (NACT) followed by interval cytoreduction. Outcomes for patients offered management with LSC (post-LSC) were compared to a cohort from 2010–2012 who would have qualified for laparoscopy (pre-LSC). Summary statistics were used to describe surgical outcomes, and DFS and OS were estimated using the Kaplan-Meier method. Results: Between 2013–2016, 201 OC patients were offered LSC; 182 underwent laparoscopy. We identified 161 pre-LSC control patients for comparison. There were no differences in clinicodemographic features between both cohorts. Prior to implementing LSC, 64 (40%) patients underwent PDS compared to 88 (44%) post-LSC (p=0.42). Complete cytoreduction (R0) was achieved more frequently in the post-LSC cohort (81 vs 51%, p<0.001). There were no differences in median DFS or OS between pre- and post-LSC cohorts (DFS 17 vs 16 months, p=0.76; OS 45 vs 48 months, p=0.38). However, within the PDS group, a significantly greater median OS was observed in post-LSC compared to pre-LSC cohort (not reached vs 51 months, p<0.013). Conclusion: Our data suggest that LSC allows for a greater R0 resection rate and, for patients triaged to PDS, is associated with improved median OS.